2022
DOI: 10.3390/fermentation8080409
|View full text |Cite
|
Sign up to set email alerts
|

Critical Optimized Conditions for Gamma-Aminobutyric Acid (GABA)-Producing Tetragenococcus Halophilus Strain KBC from a Commercial Soy Sauce Moromi in Batch Fermentation

Abstract: Gamma-aminobutyric acid (GABA) has several health-promoting qualities, leading to a growing demand for natural GABA production via microbial fermentation. The GABA-producing abilities of the new Tetragenococcus halophilus (THSK) isolated from a commercial soy sauce moromi were proven in this investigation. Under aerobic conditions, the isolate produced 293.43 mg/L of GABA after 5 days of cultivation, compared to 217.13 mg/L under anaerobic conditions. Critical parameters such as pH, monosodium glutamate (MSG),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
2
1
Order By: Relevance
“…laudensis MAG also contained the gadB gene but not the antiporter gadC , which is necessary for GABA production ( 43 ). Whereas GABA production by T. halophilus strains has been described before ( 44 ), the lack of correlation between T. halophilus and GABA production and the absence of the necessary genes in the T. halophilus MAG retrieved in the present study suggested that GABA production was a strain-dependent feature for this species.…”
Section: Discussioncontrasting
confidence: 66%
“…laudensis MAG also contained the gadB gene but not the antiporter gadC , which is necessary for GABA production ( 43 ). Whereas GABA production by T. halophilus strains has been described before ( 44 ), the lack of correlation between T. halophilus and GABA production and the absence of the necessary genes in the T. halophilus MAG retrieved in the present study suggested that GABA production was a strain-dependent feature for this species.…”
Section: Discussioncontrasting
confidence: 66%
“…This model has a non-significant Lack of Fit with a p -value of 0.6137 ( p > 0.05). With all these values, the overall quality and the reliability of this model in predicting the GABA production yield is highly acceptable [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Korean traditional fermented kimchi leads the chart with anti-tumor effect, which could lead to the potential key antibody in generating anti-tumor necrosis factor (TNF) COVID-19 therapy. Meanwhile, the Malaysian kicap contains key immune-booster compound called gamma-aminobutyric acid (GABA) (Sassi et al, 2022), which provides first-line defense in combatting the initial exposure to COVID-19. The Chinese douchi provides a strong antioxidant effect both in in vivo and in vitro (Wang et al, 2008) which can reduce oxidative stress and inflammatory responses of infected organs of COVID-19 patients.…”
Section: Prominent Plant-based Fermented Foods In Asia and Covid-19 F...mentioning
confidence: 99%